Erythropoietin for Cognitive Deficits Associated with Schizophrenia, Bipolar Disorder, and Major Depression: A Systematic Review - Li, Xian-Bin; Zheng, Wei; Ning, Yu-Ping; Cai, Dong-Bin; Yang, Xin-Hu; Ungvari, Gabor S.; Ng, Chee H.; Wang, Chuan-Yue; Xiang, Yu-Tao (Pharmacopsychiatry, 2018)
Introduction The purpose of this study is to systematically review the efficacy and safety of adjunctive erythropoietin (EPO) in treating cognitive deficits associated with schizophrenia, bipolar disorder, and major depression based on randomized controlled trials (RCTs).Methods Two evaluators independently and systematically searched and selected studies, extracted data, and conducted quality assessment.Results Four RCTs with 144 patients (71 in the EPO group and 73 in the placebo group) met the study entry criteria. Adjunctive EPO could improve schizophrenia-related cognitive performance. In patients with bipolar disorder, EPO could also enhance sustained attention, recognition of happy faces, and speed of complex information processing across learning, attention, and executive function when compared with placebo. In addition, EPO could enhance verbal recall, recognition, and memory in patients with major depression.Discussion This preliminary study found that adjunctive EPO appears to be effective in treating cognitive deficits associated with schizophrenia, bipolar disorder, and major depression without major adverse effects observed. Further higher quality RCTs with larger samples are needed to confirm the findings.Review registration: CRD42017058094
Keywords: erythropoietin; cognitive function; schizophrenia; bipolar disorder; major depression